Water-Based Exercises on Peak Oxygen Consumption, Exercise Time, and Muscle Strength in Patients with Coronary Artery Disease: A Systematic Review with Meta-Analysis - Alana Lalucha Andrade Guimarães; Mansueto Gomes-Neto; Lino Sérgio Rocha Conceição; Micheli Bernardone Saquetto; Caroline Oliveira Gois; Vitor Oliveira Carvalho (Cardiovascular Therapeutics)
Background. There is a growing use of water-based exercises in cardiac rehabilitation programs. However, there is little data concerning the effects of water-based exercise on the exercise capacity of coronary artery disease (CAD) patients. Objective. To perform a systematic review to investigate the effects of water-based exercise on peak oxygen consumption, exercise time, and muscle strength in patients with CAD. Methods. Five databases were searched to find randomized controlled trials that evaluated the effects of water-based exercise for coronary artery disease patients. Mean differences (MD) and 95% confidence intervals (CIs) were calculated, and heterogeneity was assessed using the I2 test. Results. Eight studies were included. Water-based exercise resulted in an improvement in peak VO2 of 3.4 mL/kg/min (95% CI, 2.3 to 4.5; I2=0%; 5 studies, N=167), exercise time of 0.6 (95% CI, 0.1 to 1.1; I2=0%; 3 studies, N=69), and total body strength of 32.2 kg (95% CI, 23.9 to 40.7; I2=3%; 3 studies, N=69) when compared to no exercising controls. Water-based exercise resulted in an improvement in peak VO2 of 3.1 mL/kg/min (95% CI, 1.4 to 4.7; I2=13%; 2 studies, N=74), when compared to the plus land exercise group. No significant difference in peak VO2 was found for participants in the water-based exercise plus land exercise group compared with the land exercise group. Conclusions. Water-based exercise may improve exercise capacity and should be considered as an alternative method in the rehabilitation of patients with CAD.